Red cell exchange for patients with sickle cell disease: an international survey of current practices. Issue 7 (24th June 2020) - Karafin, Matthew S.; Hendrickson, Jeanne E.; Kim, Haewon C.; Kuliya‐Gwarzo, Aisha; Pagano, Monica B.; Perumbeti, Ajay; Shi, Patricia A.; Tanhehco, Yvette C.; Webb, Jennifer; Wong, Edward; Eichbaum, Quentin
ABSTRACT: INTRODUCTION: Red cell exchange (RCE) therapy is increasingly used to treat patients with acute or chronic manifestations of sickle cell disease (SCD). However, little is known regarding the most safe and effective practice parameters associated with this particular therapy. METHODS: A SCD subcommittee of members of the American Society for Apheresis (ASFA) developed a 122‐question survey and administered it via email to other ASFA members. The survey inquired about clinical indications for treatment, practice patterns, and transfusion policies for RCE when used for patients with SCD. RESULTS: Ninety‐nine distinct institutions completed the survey. Twenty‐one (21%) were from outside of the US. Twenty‐two (22%) provided chronic transfusion therapy to >10 patients, and both adult (25%) and pediatric‐focused services (20%) were represented. Common acute indications for RCE included acute chest syndrome, acute ischemic stroke, and pre‐surgical prophylaxis. Common chronic indications included primary stroke prophylaxis, secondary stroke prophylaxis, and recurrent acute chest syndrome. Respondents most commonly set a post‐RCE treatment target of 30% for the hematocrit and hemoglobin S levels, regardless of the therapeutic indication. Units for RCE were phenotypically matched in 95% of cases. About 40% of respondents reported using isovolemic hemodilution. CONCLUSIONS: This survey solicited the current practice variations in RCE from a diverse range of practice sites. Many sites reported similar practice patterns and challenges but some variations emerged. To our knowledge, this survey represents the largest and most in‐depth investigation of the use of RCE for patients with SCD, and could inform future studies in the field.